Pd Ultra‐Small Clusters as Precursors for Silica‐Encapsulated Pd Nanoreactors: Highly Sinter‐Resistant Catalysts. Issue 7 (6th May 2013) - Samanta, Anupam; Devi, R. Nandini
Abstract Sintering and consequent deactivation in supported metal catalysts is a severe problem encountered in heterogeneous catalysis. This problem can be addressed by encapsulating active metal nanoparticles within inert oxides such as silica, provided the oxide shell is porous to enable access of reactant molecules to the nanoparticle surface to facilitate catalysis. We report the synthesis of highly sinter‐resistant silica‐encapsulated Pd catalysts with nanoparticle sizes stabilized at (3.4±0.6) nm at high temperatures of approximately 750 °C. The synthesis was achieved by utilizing thiol‐protected ultra‐small clusters of Pd as precursors for silica encapsulation. The ultra‐small clusters were synthesized by using propyl ammonium functionalised thiols making them water‐dispersible and amenable for silica encapsulation. Abundance of organics also aided in creating porosity subsequent to calcination at high temperatures.